2003
DOI: 10.1097/00002093-200310000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Advance Directives for Health Care and Research

Abstract: Patients suffering from Alzheimer disease and other types of dementia gradually lose their decision-making capacity. Advance directives have been widely promoted as a means to maintain some control over one's life in the event of decisional incompetence. This study used data from a recent postal survey conducted in Quebec, Canada to: 1) estimate the prevalence of formal and informal advance directives for health care and research among community-dwelling older adults presumed free of cognitive deficits; and 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 46 publications
3
55
0
1
Order By: Relevance
“…Characteristics that were investigated more frequently and more consistently found to be associated with ADs completion are rather those that lacked association in our study including older age (e.g. [9, 34, 35, 38]), female gender (e.g. [21, 35, 38]), not living in the community (e.g.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Characteristics that were investigated more frequently and more consistently found to be associated with ADs completion are rather those that lacked association in our study including older age (e.g. [9, 34, 35, 38]), female gender (e.g. [21, 35, 38]), not living in the community (e.g.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies, for example, identified completion of ADs to be also positively associated with characteristics like higher income [34], having a regular source of care [34], preparation of other planning documents [5], knowing someone with cognitive impairment [38], and having not recently experienced the death of a relative or acquaintance [32, 35]. The impact of such characteristics, however, was investigated only in few or single studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although advance directives are mentioned in most policy discussions, the rates of completion of research advance directives are likely to remain low. 31,32 One study found that even among a highly motivated group of people—people already engaged in a clinical research study for first-degree relatives of patients with AD and most of whom expressed a willingness to complete advance directives—only 16% completed a research advance directive during the year following the survey. 32 …”
Section: Autonomy and Consent Capacitymentioning
confidence: 99%
“…A diagnosis of dementia was likely to prompt planning, while a more acute diagnosis such as an illness likely to result in death within a short period of time was less likely to inspire future planning, with living for the moment being the focus instead [12]. Other research showed that seeing other people experience issues with their health or cognition did promote the establishment of future plans [13,14].…”
Section: Resultsmentioning
confidence: 99%